The Relationship of Work Environment, Organizational Culture, and Employee Welfare to Financial Performance - Rifai, Mesrawati; Makduani, Rivai; Krisnanto, Budhi; Panus, Panus; Lawalata, Izaac L D (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This study investigates the relationship between the work environment, organizational culture, and employee welfare and their impact on financial performance. The research aims to comprehensively understand how these elements individually and synergistically influence organizational success, addressing gaps in prior literature. Research Design and Methodology: To synthesize insights from existing studies, a qualitative approach utilizing a Systematic Literature Review (SLR) was employed. The review identified trends, patterns, and theoretical underpinnings connecting the work environment, organizational culture, and employee welfare with financial outcomes. Data were derived from peer-reviewed articles and theoretical frameworks such as Social Exchange Theory (SET) and the Resource-Based View (RBV). Findings and Discussion: The study confirms that the work environment significantly affects productivity and efficiency, with physical, social, and psychological factors playing crucial roles. Organizational culture fosters innovation, adaptability, and collaboration, enhancing competitiveness and operational success. Employee welfare, encompassing physical, mental, and financial well-being, directly impacts employee retention, engagement, and cost efficiency. The synergy among these elements creates a holistic system that drives sustainable financial performance and competitive advantage. The findings underscore the need to integrate these factors into organizational strategies to optimize human capital. Implications: This study offers practical guidance for managers and policymakers in designing evidence-based interventions to enhance financial outcomes through strategic human capital investments. Recommendations include fostering ergonomic workspaces, building adaptive organizational cultures, and prioritizing comprehensive welfare programs. Future research should explore empirical validations and examine the impact of technological advancements on these relationship